2018
DOI: 10.1371/journal.pone.0206815
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid facilitates binding and cytotoxic activity of the pore-forming Clostridium perfringens NetF toxin to host cells

Abstract: NetF-producing type A Clostridium perfringens is an important cause of canine and foal necrotizing enteritis. NetF, related to the β-sheet pore-forming Leukocidin/Hemolysin superfamily, is considered a major virulence factor for this disease. The main purpose of this work is to demonstrate the pore-forming activity of NetF and characterize the chemical nature of its binding site. Electron microscopy using recombinant NetF (rNetF) confirmed that NetF is able to oligomerize and form large pores in equine ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In addition to affecting bacterial colonization, NanI can enhance the activity of α-toxin that causes gas gangrene (Flores-Díaz et al, 2005;Chiarezza et al, 2009), while also increasing the cytotoxicity of β-and ε-toxins and NetF and CPE toxin associated with gastrointestinal diseases (Li et al, 2011;Mehdizadeh Gohari et al, 2018;Theoret et al, 2018). Although many C. perfringens pathogenic strains only produce a small amount of CPB, CPE, or ETX (Collie et al, 1998;Sayeed et al, 2005;Fisher et al, 2006;Fernandez-Miyakawa et al, 2007;Ma et al, 2014), and the enhancement effect of natural levels of NanI on CPB, CPE and ETX is relatively moderate (1.5-2-fold), this activity may be important for the pathogenesis of C. perfringens during enteritis or enterotoxemia.…”
Section: Effects Of Sialidases On the Cytotoxicity Of C Perfringensmentioning
confidence: 99%
“…In addition to affecting bacterial colonization, NanI can enhance the activity of α-toxin that causes gas gangrene (Flores-Díaz et al, 2005;Chiarezza et al, 2009), while also increasing the cytotoxicity of β-and ε-toxins and NetF and CPE toxin associated with gastrointestinal diseases (Li et al, 2011;Mehdizadeh Gohari et al, 2018;Theoret et al, 2018). Although many C. perfringens pathogenic strains only produce a small amount of CPB, CPE, or ETX (Collie et al, 1998;Sayeed et al, 2005;Fisher et al, 2006;Fernandez-Miyakawa et al, 2007;Ma et al, 2014), and the enhancement effect of natural levels of NanI on CPB, CPE and ETX is relatively moderate (1.5-2-fold), this activity may be important for the pathogenesis of C. perfringens during enteritis or enterotoxemia.…”
Section: Effects Of Sialidases On the Cytotoxicity Of C Perfringensmentioning
confidence: 99%
“…The ability of NetF to form pores in biological membranes has been investigated, as well as the host cell surface receptor for NetF or some of its major characteristics; NetF is able to oligomerize and form pores with 6–8 subunits in biological cell membranes such as sheep erythrocytes and EO cells. 42 The defined size of the NetF pore was estimated to be ~4–6 nm. NetF pores are very similar in size to C. perfringens delta-toxin pores with a functional diameter of 5 nm, 33 but are larger than NetB pores (1.8 nm) and S. aureus alpha-toxin pores (2.8 nm).…”
Section: Introductionmentioning
confidence: 99%
“…16,25 In addition, a cell surface sialoprotein(s) most likely plays a crucial role in binding or cytopathic activity of NetF. 42 However, further work is required to identify the host cell surface receptor(s) for NetF because identification could not only improve understanding of the mode of action and host-specificity of this toxin but it might also lead to the development of therapeutic or preventive approaches that target the activity of NetF.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that NetF binds to a sialoprotein(s) on the surface of biological membranes and form pores containing 6–8 NetF monomers [ 73 ]. Osmotic protection assay results revealed that the NetF pore has a functional diameter of ~4-6 nm in RBCs and equine ovarian cell lines, which is larger than the NetB pore (1.8 nm) and S. aureus alpha-toxin pore (2.8 nm) [ 58 , 73 , 74 ].…”
Section: Proven or Potential Virulence Factorsmentioning
confidence: 99%
“… 36 - - pCW3-like plasmid α-clostripain Cysteine Protease ? 59.6 - - Chromosome a Compiled from [ 6 , 8 , 22 , 37 , 45 , 59 , 64 , 68 , 72 , 82 , 255 , 293–296 ] b Compiled from [ 5 , 28 , 31 , 36 , 58 , 60 , 68 , 73 , 78 , 297–301 ] c Compiled from [ 12 , 62 , 109 , 112 , 115 , 120 , 123 , 136–144 , 302 , 303 ] …”
Section: Introductionmentioning
confidence: 99%